Acetate Induces Growth Arrest in Colon Cancer Cells Through Modulation of Mitochondrial Function - Sahuri-Arisoylu, Meliz; Mould, Rhys R.; Shinjyo, Noriko; Bligh, S. W. Annie; Nunn, Alistair V. W.; Guy, Geoffrey W.; Thomas, Elizabeth Louise; Bell, Jimmy D. (Frontiers in Nutrition, 2021)
Acetate is one of the main short chain fatty acids produced in the colon when fermentable carbohydrates are digested. It has been shown to affect normal metabolism, modulating mitochondrial function and fatty acid oxidation. Currently, there is no clear consensus regarding the effects of acetate on tumorigenesis and cancer metabolism. Here, we investigate the metabolic effects of acetate on colon cancer. HT29 and HCT116 colon cancer cell lines were treated with acetate and its effect on proliferation, reactive oxygen species, cellular bioenergetics, gene expression of acetyl-CoA synthetase 1 (ACSS1) and 2 (ACSS2) and lipid levels were investigated. Acetate was found to reduce proliferation of both cell lines under normoxia as well as reducing glycolysis; it was also found to increase both oxygen consumption and ROS levels. Cell death observed was independent of ACSS1/2 expression. Under hypoxic conditions, reduced proliferation was maintained in the HT29 cell line but no longer observed in the HCT116 cell line. ACSS2 expression together with cellular lipid levels was increased in both cell lines under hypoxia which may partly protect cells from the anti-proliferative effects of reversed Warburg effect caused by acetate. The findings from this study suggest that effect of acetate on proliferation is a consequence of its impact on mitochondrial metabolism and during normoxia is independent of ACCS1/2 expression.